Low temperature sintered cordierite ceramics from MgO-Al2O3-SiO2 glass powder - Xiao, Zhuohao (2020)
Cordierite ceramics are widely used in electronic and information fields due to their excellent electrical, thermal and mechanical properties. In the present work, cordierite ceramics with both low coefficient of thermal expansion (CTE) and high flexural strength were successfully derived from MgO-Al2O3-SiO2 glass powder. The effects of sintering temperature on phase composition and microstructure of the ceramics were elaborated, while the relationships among sintering temperature, CTE, mechanical strength and density were comprehensively discussed. It has been shown that the MgO-Al2O3-SiO2 glass powder can be well sintered into cordierite ceramics at temperatures in the range of 1050-1150°C, which are much lower than the commonly reported sintering temperatures that are over 1400°C. Specifically, the cordierite ceramic sample sintered at 1150°C exhibits a CTE of 2.123×10-6 °C-1 and a flexural strength of 97.05 MPa.